Studi Parameter ModelPenangkap Angin Pada Sistem TowerPendinginan Evaporasi Menggunakan CFD Untuk Mendapatkan Laju optimal Udara - Abdullah, Abdullah; , Ir. Sarjito, MT, Ph.D; , Nur Aklis,ST,M.Eng (2017)
This research is an extension of previous researchers about wind catcher using computational fluid dynamic (CFD). The previous research did not use baffle variations. The aim of the research work was to compare two type ability of wind catcher in obtaining optimum mass flow rate. The first type was wind catcher was designed without baffle and second type was wind catcher designed using baffle that consisted of; wind catcher with cylinder baffle, square baffle, plus with four holes baffle, and combined wind catcher with eight holes baffle. Simulation was carried out in vary of incoming wind speed of 0.5m/s to 5m/s at 11,5m height. Due to the complexity of geometry then unstructured mesh was adopted. The wind catcher without baffle resulted total element of 1237341, whereas, wind catcher with cylinder baffle resulted in 2090432 element, square baffle resulted element of 2366514, baffle plus resulted in element of 4425278, and combined baffle produced element of 7747840. Initially, The k-epsilon turbulen model was selected in this simulation as it is robust in time. The parametric study of wind catcher model was carried out in two steps; the first step was comparing performa of five shape of wind catcher. Where, the wind catcher with four holes with plus baffle resulting optimum mass flow rate, and the second performance was demonstrated by studying effect of extension baffle. In this study, wind catcher was modified by extending baffle of 1m. Result of the comparison study showed that wind catcher with one extension baffle resulted an optimal performance. Further simulation was by investigating different inflation boundary layer and different turbulen model. In studying inflation boundary layer, total maximum of layer was varying from: 5, 10, 15, dan 20 at wind speed of 5 m/s. The optimum performance was reached by maximum layer of 10. The study of turbulence model was carried out at all simulation involved k-epsilon, Shear Stress Transport, BSL Reynold Stress, dan SSG Reynold Stress turbulence model. The wind speed was set as same as in studying inflation boundary layer of 5 m/s. The Studi showed that SSG Reynold Stress turbulen model was able to reach an optimum performance. All simulation was carried out using ANSYS,version 15.0.